2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7592107
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory alloy smart knee spacer to enhance knee functionality: Model design and finite element analysis

Abstract: In this paper we introduce Shape Memory Alloy (SMA) for designing the tibial part of Total Knee Arthroplasty (TKA) by exploiting the shape-memory and pseudo-elasticity property of the SMA (e.g. NiTi). This would eliminate the drawbacks of the state-of-the art PMMA based knee-spacer including fracture, sustainability, dislocation, tilting, translation and subluxation for tackling the Osteoarthritis especially for the aged people of 45-plus or the athletes. In this paper a Computer Aided Design (CAD) model using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The elastic modulus of Nitinol used in this study was only approximately 30 GPa, which was lower than that reported in the literatures [36,37,38]. In Taiwan, the available source of the Nitinol alloy is rarer than those of the commonly used titanium and stainless steel alloys.…”
Section: Discussionmentioning
confidence: 61%
“…The elastic modulus of Nitinol used in this study was only approximately 30 GPa, which was lower than that reported in the literatures [36,37,38]. In Taiwan, the available source of the Nitinol alloy is rarer than those of the commonly used titanium and stainless steel alloys.…”
Section: Discussionmentioning
confidence: 61%
“…However, most researchers adopt the finite element modeling to analyze the total knee joint. Authors in [13] studied the causes of valgus deformity in TKA, and the finite element analysis of using a rotating total knee prosthesis is discussed in [14]. There is little literature on finite element analysis of UKA prosthesis, because UKA is a minimally invasive surgery, which prevents effective finite element pressure scanning.…”
Section: Introductionmentioning
confidence: 99%